2017
DOI: 10.3390/ijerph14030286
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stigma of Sudden Bereavement as a Risk Factor for Suicidal Thoughts and Suicide Attempt: Analysis of British Cross-Sectional Survey Data on 3387 Young Bereaved Adults

Abstract: The sudden death of a friend or relative, particularly by suicide, is a risk factor for suicide. People who experience sudden bereavement report feeling highly stigmatised by the loss, potentially influencing access to support. We assessed whether perceived stigma following sudden bereavement is associated with suicidal thoughts and suicide attempt. We analysed cross-sectional survey data on 3387 young adults bereaved by the sudden death of a close contact. We tested the association of high versus low perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 42 publications
(56 reference statements)
5
52
0
Order By: Relevance
“…Consistent with the findings of previous studies, we found that shame was related to suicidal ideation in our undergraduate sample. The cross-sectional surveys among British young adults [67] and Chinese undergraduates [25] showed similar conclusions. Due to the pressure of the college entrance examination in Chinese universities, academic achievement has been prioritized over mental health in most of the elementary and secondary schools.…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with the findings of previous studies, we found that shame was related to suicidal ideation in our undergraduate sample. The cross-sectional surveys among British young adults [67] and Chinese undergraduates [25] showed similar conclusions. Due to the pressure of the college entrance examination in Chinese universities, academic achievement has been prioritized over mental health in most of the elementary and secondary schools.…”
Section: Discussionsupporting
confidence: 55%
“…Research shows that people bereaved by unnatural causes feel more stigmatised than those bereaved by natural causes [50], and that this stigma is implicated in adverse mental health outcomes [34]. The stigma of sudden bereavement is itself a risk factor for suicide attempt [51], with findings from qualitative [52] and quantitative [26] research suggest that this stigma can limit support from others [50]. By marketing support services to encourage young people bereaved by unnatural causes to access support for substance misuse and other difficulties, this stigma would be challenged whilst also encouraging help-seeking.…”
Section: Clinical Policy and Research Implicationsmentioning
confidence: 99%
“…We also suggested various explanations for the association between suicide bereavement and suicide attempt, based on the literature and clinical observation [ 2 ]. These included: the psychological trauma of a suicide loss; shared familial or environmental vulnerabilities to mental illness and suicidality; the influence of stigma [ 12 ] on help-seeking; and suicide suggestion [ 13 ]. The last of these describes the impact of a role model’s suicide or suicide attempt on a person’s internal constraints against self-harm, [ 14 ] whether due to social learning, imitation or emotional contagion [ 13 ].…”
Section: Introductionmentioning
confidence: 99%